China and ASEAN-5 in trade - friends or foes? - Koh, Lee Huang. (2008)
A study of export competitiveness among China and the ASEAN-5 countries. Impact of 1985, 1994, 1997 economic events are investigated. Competition existed in the primary and manufactured products. Analysis shows that bilateral trade is increasing rapidly.